JADID'S VIEWS ON TEACHING "ISLAMIC HISTORY" IN SCHOOLS (World Bulletin of Social Sciences, 2024)
This article analyzes Mahmudhoja Behbudi, Jadidism, Jadid schools, and the activities of enlightened scientists, sciences.